'Just leave it blank' non-religious children and their negotiation of prayer in school. Issue 4 (1st October 2020) - Shillitoe, Rachael; Strhan, Anna
ABSTRACT: This article examines how non-religious children experience acts of collective worship and prayer in primary school settings and analyses how they negotiate religion and their non-religious identities in these events. Drawing on ethnographic fieldwork examining non-religious childhoods and collective worship in three English primary schools, the authors explore how non-religious children demonstrate their agency when confronted with particular boundaries and concepts related to religion and non-religion in school contexts. Attending to the experiences, perspectives, and practices of non-religious children adds to our understanding of the varieties of non-religion, which has to date largely focused on elite, adult populations. Focusing on non-religious children's experiences of prayer reveals how these children did not experience tensions between praying to God and their non-religious identities and articulated their own interpretations of these practices, deepening understanding of the lived realities of non-religious cultures and identities.